2021
DOI: 10.1051/0004-6361/202039626
|View full text |Cite
|
Sign up to set email alerts
|

Synthesising the repeating FRB population using frbpoppy

Abstract: The observed fast radio burst (FRB) population can be divided into one-off and repeating FRB sources. Either this division is a true dichotomy of the underlying sources, or selection effects and low activity prohibit us from observing repeat pulses from all constituents making up the FRB source population. We attempted to break this degeneracy through FRB population synthesis. With that aim in mind, we extended frbpoppy (which previously only handled one-off FRBs) to also simulate repeaters. We next modelled t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…However, at present only 20 repeating sources are published and the overall fraction of repeating sources in the FRB population is unknown. Whether all FRBs eventually repeat is an open question, one that is being tackled currently both with observational efforts (Fonseca et al 2020) and modelling (Gardenier et al 2019(Gardenier et al , 2021.…”
Section: Time Domain Surveysmentioning
confidence: 99%
“…However, at present only 20 repeating sources are published and the overall fraction of repeating sources in the FRB population is unknown. Whether all FRBs eventually repeat is an open question, one that is being tackled currently both with observational efforts (Fonseca et al 2020) and modelling (Gardenier et al 2019(Gardenier et al , 2021.…”
Section: Time Domain Surveysmentioning
confidence: 99%
“…However, it is still under hot debate whether genuinely non-repeating FRBs exist (Caleb et al 2018(Caleb et al , 2019Palaniswamy et al 2018;Xiao et al 2021). A few works have discussed the possibility to judge this question using the number fraction of repeaters (Caleb et al 2019;Lu et al 2020;Ai et al 2021;Gardenier et al 2021). With the accumulation of observing time, this fraction will increase to 100% if all FRBs turn out to be repeating.…”
Section: Introductionmentioning
confidence: 99%
“…Still, it is fair to argue that all FRBs repeat on the supposition that their repeating modes are diverse. Several studies have tried to reproduce the observed statistical properties with different models of repeating [154,155]. For instance, the difference in pulse width distribution can be ascribed to FRB beaming [156].…”
Section: Repeating and Non-repeating: A Single Population?mentioning
confidence: 99%
“…Generally, with the accumulation of the observing time, the observed repeating fraction (defined as the number ratio of repeaters among all FRBs) is expected to increase to nearly 100% [124,151,157]. However, if there exist physically non-repeating FRBs, this fraction will peak at a certain observing time and the peak fraction is less than 100% [154,157]. The current total observing time of CHIME may be still insufficient to bring out the peak.…”
Section: Repeating and Non-repeating: A Single Population?mentioning
confidence: 99%
See 1 more Smart Citation